Non-viral gene transfer to the tendon: comparison of two methods - Melendez, Matias; Lagranha, Valeska Lizzi; Baptista, André; Lompa, Paulo Arlei; Giugliani, Roberto; Matte, Ursula (Clinical and Biomedical Research, 2012)
Background: tendons are part of the connective tissue that joins muscle to bone. Tendon injuries are a problem, since they have a poor ability to regenerate spontaneously. Alternative treatments involving the injection of local growth factors and gene transfer has been evaluated. Thus, we compared two methods for non-viral gene transfer tendons, using the GFP gene as reporter gene. Methods: Wistar rats had the medial quadriceps tendon exposed and the plasmid was transferred by direct injection or complexed with liposomes. Quantification of GFP in the tendom and in the spleen was evaluated by histological analysis with a fluorescence microscope. Results: gene transfer to the tendon was successfully obtained in both treatments. Lipoplex, as expected, showed the highest efficiency in transducing tenocytes, however we have found GFP expression also in the spleen. Naked DNA also showed fluorescence values above the control group and the signal was limited to the tendom. Discussion: the use of GFP as a reporter gene is a classical approach to evaluate gene transfer efficiency. Non-viral gene transfer methods are safe but show low levels of transduction and transient expression. For tendon repair, however, these characteristics may prove beneficial because a transient expression may be desirable to avoid the risk of adverse effects. GFP distribution in the spleen was probably a result of lipoplexes uptake by cells from the reticular endothelial system. Conclusion: taking into account the distribution of GFP in another tissue when using lipoplex, we believe that naked DNA is a more appropriate way to perform gene transfer to the tendon, ensuring safety, low cost and easy handling.